Moderasi Beragama: Melacak Nilai Moderasi dalam Term al-Hamd Perspektif Abdul Kalam Azad - Cahyani, Nadia Saphira; Rohmah, Miftahur (Jalsah : The Journal of Al-quran and As-sunnah Studies, 2022)
This article discusses the value of religious moderation in Abul Kalam Azad in QS al-Fatihah. The value of moderation is implied in the al-hamd which describes the nature of divinity in growing humanity. The problem formulation of this article is how is Abul Kalam Azad's interpretation related to QS al-Fatiah And how is the contextualization of this interpretation if it is applied in the realm of Indonesia. This article is a literature study using the analytical-descriptive method of data related to the study theme. The findings from this article are that the main religious concept of Abul Kalam Azad in QS al-Fatihah which consists of mahmud, Al-hamd, Rab al-alamin, Maliki yaum al-din, sirat al- Mustaqim there is a value of religious moderation that fosters tolerance of religious harmony implied in the al-hamd. This article confirms the interpretation of al-hamd as the concept of humanizing humans which is contextualized in the realm of Indonesia. Thus, it is very relevant to grow an interpretation based on the value of religious moderation in Indonesia.